METHODS OF TEACHING VOCABULARY FOR THE ELEMENTARY LEVELS - Normatova Yulduz Nurnazarovna (Galaxy International Interdisciplinary Research Journal, 2022)
From this paper work we discuss methods of teaching vocabulary for elementary students and also, we must know that development of a student's language and communication abilities is dependent on his or her vocabulary.